Tibial tubercle osteotomy for the exposure of complex primary and revision Total Knee Arthroplasty- our 21 years of experience - Ameya Katariya; P. Suryanarayan; Vijay Bose; P.S. Ashok Kumar; Kalaivanan Kanniyan; Shantanu Patil (Journal of Orthopaedic Reports)
Abstract-: Background: Adequate exposure is often challenging in complex primary and revision Total Knee Arthroplasty (TKA). A quadriceps snip in addition to a standard approach is the most widely used approach in such cases. Tibial tubercle osteotomy (TTO) becomes an attractive option where a quadriceps snip is inadequate and a more extensile approach is required. However, due to multiple reported complications and lack of clear consensus regarding surgical technique, there is reluctance to the use of this approach. Methods: We retrospectively analysed 30 cases of TTO operated between January 2002 to January 2023, by two surgeons but with the same surgical technique and rehabilitation protocol. Study included 9 cases of complex primary and 21 cases of revision TKAs. Mean age was 57 years (29–77 years) with a mean follow up of 14 years (3–21 years). Rehabilitation was individualised according to wound status and function. At follow ups knee range of motion, extensor lag, mobility status, gait, status of the wound, osteotomy union rate and proximal migration was recorded. Results: Arc of motion improved from a mean 42° (Range, 15 to 60) preoperatively to a mean 89° (Range, 50 to 110) post operatively. 29 osteotomies (96.66 %) united in a mean duration of 4.6 months (1.5–8 months). Two patients (6.66 %) had extensor lag with a mean of 10°. Five osteotomies (16.66 %) had proximal migration with a mean of 4 mm (2–6 mm) and two cases (6.66 %) had patella Baja. No wound healing problems, dehiscence or fractures were reported in early and late post-operative period. Conclusion: TTO is an effective, safe and reliable approach for a complex primary or revision TKA. However, good surgical technique and titrated rehabilitation program remain the key to achieve good post-operative function and minimise complications.